The Importance of Situational Awareness: A Qualitative Study of Family Members' and Nurses' Perspectives on Teaching During Family-Centered Rounds. (October 2015) - Beck, Jimmy; Meyer, Rebecca; Kind, Terry; Bhansali, Priti
Abstract : Purpose: Family-centered rounds (FCR) has become a leading model for pediatric inpatient rounding. During FCR, faculty must balance trainees' educational needs with patient care priorities. Investigators have examined trainees' views on effective teaching during FCR, but none have evaluated what family members and nurses consider to be effective teaching behaviors of attending physicians. The authors sought to explore family members' and nurses' perspectives on effective teaching behaviors during FCR. Method: The authors conducted (2012–2013) a qualitative study of families and nurses at an academic children's hospital where FCR is the standard model for inpatient rounds. Nurses and families familiar with FCR participated in separate focus groups. The authors reviewed focus group transcripts using techniques of qualitative content analysis; they generated codes and developed categories, supported by illustrative quotations. Results: Fifteen nurses and 13 family members participated in the focus groups. The unifying theme was that situational awareness on behalf of the attending physician is essential for FCR to be educational for all participants. The authors identified four categories of awareness—(1) cognitive factors, (2) logistics and time management, (3) physical environment, (4) emotional state—and developed a set of effective teaching strategies based on participants' comments. Conclusions: The findings of this study support previous work identifying effective FCR teaching strategies, but this study is the first to include the perspectives of families and nurses. The inclusion of these participants provides a framework for faculty development and training to improve the educational value of FCR. Abstract : Supplemental Digital Content is available in the text.